Personal factors that influence coffee purchase intention among young adults in Johor Bahru - Norazami, Noraisah; Nik Azwaddi, Nik Nurain Nadirah; Rahman, Razman; Abdullah, Rahman; Husin, Norhayati (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
The coffee consumption culture has become an integral part of urban Malaysian daily life, especially among young adults. This is apparent in Johor Bahru, where coffee culture is inextricably connected with urban living and shifting consumer trends. This paper explores personal factors that drive coffee purchase intention among young adults in Johor Bahru. A total of 380 respondents were surveyed through purposive and convenience sampling strategies. Five personal factors; (1) age and life cycle, (2) occupation, (3) income, (4) lifestyle, and (5) personality contribute significant influences toward purchase intention, which were found through these results. Among these, personality was found to be the strongest factor. Personality traits, such as openness and extraversion, were found to play a significant role in influencing consumer choices, followed by lifestyle choices based on social identity and routine behaviour. Therefore, personal factors are a critical consideration for coffee businesses seeking heightened customer commitment and market strategy. Business operators and marketers need to customise their strategies according to young people's preferred choices and characteristics, especially those primarily concentrated in urban areas such as Johor Bahru, in order for them to remain competitive and sensitive to changing customers' needs in the marketplace.